Comparison of Conventional Play Therapy Methods and Educational Videos on Social Skills in Children with Intellectual Disabilities - Hidayat, Shulhan Arief (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Children with intellectual disabilities face problems in intellectual and adaptive functioning that arise during development, especially in social skills. One of the effective strategies for dealing with non-adaptive social interactions in children with intellectual disabilities is play therapy. This study aims to look at the comparison of conventional play therapy methods and educational videos on social skills in children with intellectual disabilities. This research . The research sample consisted of 36 students from Primary Extraordinary School C, Tulungagung Regency, who were divided into two groups. The research instrument used social skills observation sheets with statistical tests using the Independent t test. The results showed that there was a comparison of social skills in respondents who used play therapy with the conventional puzzle method and origami educational videos which showed a significance value of p=0.048 (Pvalue <0.05). The use of instructional videos can also increase children's enthusiasm for learning. Therefore, audio-visual media, such as videos, can be an effective tool in improving the social skills of children with intellectual disabilities.